Naja annulifera Snake: New insights into the venom components and pathogenesis of envenomation. - Felipe Silva-; Isadora Maria Villas-Boas; Solange Maria de Toledo Serrano; Bruno Cogliati; Sonia Aparecida de Andrade Chudzinski; Priscila Hess Lopes; Eduardo Shigueo Kitano; Cinthya Kimori Okamoto; Denise V Tambourgi (Public Library of Science (PLoS), 2019)
Background Naja annulifera is a medically important venomous snake occurring in some of the countries in Sub-Saharan Africa. Accidental bites result in severe coagulation disturbances, systemic inflammation and heart damage, as reported in dogs, and death, by respiratory arrest, in humans. Despite the medical importance of N. annulifera, little is known about its venom composition and the pathogenesis of envenomation. In this paper, the toxic, inflammatory and immunogenic properties of N. annulifera venom were analyzed. Methodology/principal findings Venom proteomic analysis identified 79 different proteins, including Three Finger Toxins, Cysteine Rich Secretory Proteins, Metalloproteinases, Phospholipases A2 (PLA2), Hyaluronidase, L-amino-acid oxidase, Cobra Venom Factor and Serine Proteinase. The presence of PLA2, hyaluronidase, fibrinogenolytic and anticoagulant activities was detected using functional assays. The venom was cytotoxic to human keratinocytes. In an experimental murine model of envenomation, it was found that the venom induced local changes, such as swelling, which was controlled by anti-inflammatory drugs. Moreover, the venom caused death, which was preceded by systemic inflammation and pulmonary hemorrhage. The venom was shown to be immunogenic, inducing a strong humoral immune response, with the production of antibodies able to recognize venom components with high molecular weight and to neutralize its lethal activity. Conclusions/significance The results obtained in this study demonstrate that N. annulifera venom contains toxins able to induce local and systemic inflammation, which can contribute to lung damage and death. Moreover, the venom is immunogenic, an important feature that must be considered during the production of a therapeutic anti-N. annulifera antivenom.